Pathway and molecular mechanisms for malachite green biodegradation in Exiguobacterium sp. MG2. - Ji'ai Wang; Feng Gao; Zhongzhong Liu; Min Qiao; Xuemei Niu; Ke-Qin Zhang; Xiaowei Huang (PLoS ONE)
Malachite green (MG), N-methylated diaminotriphenylmethane, is one of the most common dyes in textile industry and has also been used as an effective antifungal agent. However, due to its negative impact on the environment and carcinogenic effects to mammalian cells, there is a significant interest in developing microbial agents to degrade this type of recalcitrant molecules. Here, an Exiguobacterium sp. MG2 was isolated from a river in Yunnan Province of China as one of the best malachite green degraders. This strain had a high decolorization capability even at the concentration of 2500 mg/l and maintained its stable activity within the pH range from 5.0 to 9.0. High-pressure liquid chromatography, liquid chromatography-mass spectrometry and gas chromatography-mass spectrometry were employed to detect the catabolic pathway of MG. Six intermediate products were identified and a potential biodegradation pathway was proposed. This pathway involves a series of reactions of N-demethylation, reduction, benzene ring-removal, and oxidation, which eventually converted N-methylated diaminotriphenylmethane into N, N-dimethylaniline that is the key precursor to MG. Furthermore, our molecular biology experiments suggested that both triphenylmethane reductase gene tmr and cytochrome P450 participated in MG degradation, consistent with their roles in the proposed pathway. Collectively, our investigation is the first report on a biodegradation pathway of triphenylmethane dye MG in bacteria.